Analisis Perancangan Sistem Informasi CDC Berbasis Web untuk Meningkatkan Informasi Lowongan Pekerjaan Bagi Lulusan Politeknik Piksi Ganesha Bandung - Gumelar, Rizki; Sudrartono, Tiris; Nunung, Ai (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Career Development Center (CDC) is a forum for providing preparation for entering the world of work for alumni and students who will graduate from the Piksi Ganesha Bandung Polytechnic. CDC is a strategic center that serves as a bridge between the worlds of education and industry, helping individuals design and implement successful career plans. This research uses descriptive qualitative methods. Research on the creation of the CDC (Career Development Center) can be accessed by alumni, students of the Piksi Ganesha Bandung Polytechnic and the general public who are looking for job vacancies or career paths on the website. Conclusion: The Piksi Ganesha Bandung Career Development Center website provides support and convenience for students and alumni in looking for work, news, and how to find work according to their respective expertise in their respective fields as well as to help individuals develop the skills, knowledge and resources needed to achieve career goals. The author suggests that this application can be developed by collaborating with labor providers and establishing cooperation based on the principle of benefit for each party.